2021
DOI: 10.1021/acs.langmuir.1c02304
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Crystallinity and Oxidation States of Nanoporous Anodized Tin Oxide Films Regulated by Annealing Treatment for Supercapacitor Application

Abstract: In this study, electrodeposition combined with anodization was employed to prepare a nanoporous tin oxide film on a pure copper substrate. It was found that annealing temperature played a critically significant role in regulating the crystallinity, pore size, and contents of different oxidation states of the anodized tin oxide film to affect the electrochemical performance. The study verified that SnO x films treated by optimized annealing at 500 °C with precisely controlling the nanoporous morphology and cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Regarding the chemical composition analysis (Table 5 ), EDS analysis reveals higher contents of iron and aluminum and lower oxygen concentration compared to those from non-annealed films (Table 4 ). These findings suggest the occurrence of chemical reactions within the oxide layer, i.e., the oxygen from the oxide and the surrounding air atmosphere reacts with the aluminum and iron species 50 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the chemical composition analysis (Table 5 ), EDS analysis reveals higher contents of iron and aluminum and lower oxygen concentration compared to those from non-annealed films (Table 4 ). These findings suggest the occurrence of chemical reactions within the oxide layer, i.e., the oxygen from the oxide and the surrounding air atmosphere reacts with the aluminum and iron species 50 .…”
Section: Resultsmentioning
confidence: 94%
“…Although no clear correlation between electrolyte composition and morphology can be established, several studies reported the occurrence of diffusion processes during annealing. These diffusion phenomena usually lead to the coalescence and fusion of pores, thus resulting in the formation of larger and flatter structures, such as flakes 48 50 .…”
Section: Resultsmentioning
confidence: 99%
“…At present, anodization has become a widely used technique for preparing metal oxides with various nanostructures. In addition to transition metals, some non-transition metals, like tin, have also been anodized to fabricate nanomaterials with various unique properties [203][204][205][206][207][208] . However, compared with the highly ordered AAO, the anodized films on transition metals, such as Fe, Cu and Zn, showed fewer perfect nanostructures with relatively low degrees of ordering.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of science and technology and the progress of the times, the demand of the society for high-performance materials has gradually expanded. Porous anodic oxides (PAOs) have shown considerable application potential in energy, environment, medical, and other fields due to their regular structure, large specific surface area, and ease to design. Over the years, the research on PAOs has mostly focused on the preparation process and the application of porous structures. However, there are few studies on the electrochemical anodization process of metals and the formation mechanism of porous structures. Therefore, the growth kinetic of PAO is still very controversial. Based on the field-assisted dissolution (FAD) theory and the field-assisted ejection theory, a “top-down” mining model is proposed.…”
Section: Introductionmentioning
confidence: 99%